Peran Dakwah Terhadap Kepercayaan Kembar Gaib Di Kampung Baru Desa Lalliseng Kecamatan Keera Kabupaten Wajo - Musfahira; Mustari Mustafa; Sakaruddin Mandjarreki (Jurnal Berita Sosial, 2024)
The thesis discussed the role of the wah on occult beliefs in the new village of Lalliseng, Keera district Wajo. The subject of this study is: 1). What is the cause of belief in occult twins? 2) how did the role of the dakwah as an attempt to educate people resulting from occult twin beliefs? 3) what are the obstacles to the public awareness of the occult twin beliefs?. It is a descriptive qualitative study. The study is conducted in the new village of Lalliseng, Keera district, Wajo. The study approaches sociology. As for the source of the data used in this study is the primary and secondary data source through observation, interviews and documentation. Data analysis used with data gathering, data reduction, data presentation, and deduction drawing. The results of this study suggest that: (1) the reason why belief in occult twins exists is because they had relationships with the astral (invisible) of previous families. Believed to live in another realm. It also has relationships with astral animals that are due to inheritance from their previous family and that their customs continue to this day. (2) the role of the preoccupation with the pagan twin belief in the new village of Lalliseng is so important that ustad's role as murabby and mu 'addib grow, direct, guide, mentor, and instill values in communities especially in the aqidah field by holding a regular presentation so that people can understand and teach the people about aqidah that society is so steeped in the teachings of Islam. (3) obstacles to the emergence of new village communities from the village of Lalliseng to the magical double belief of a lack of religious understanding, a lack of time, customs, and a lack of da 'i. The appeal of this study is expected of islamic scholars that efforts to do this research more deeply about the accepted and growing pre-islamic beliefs of the population to this day, particularly those related to the question of magical twins' belief (ana ' mallajang). Because people still abound in people who believe with belief have relationships with magical creatures and they vary in form and manner.